Toussaint; the Black liberator. - Syme, Ronald, 1910-1992.; Stobbs, William (New York : William Morrow and Company, 1971)
A biography of the eighteenth-century slave who led his people in the struggle for an independent Haiti.
The Secret Rebel -- Spanish Sanctuary -- The Divided People -- The New Allies -- The Secret Plans -- The Fall of Santo Domingo -- The Gathering Storm -- The Coming of the Enemy -- Account Paid.
Includes bibliographical references (page 192).
NLJCols20082021
Keywords: Toussaint Louverture, -- 1743-1803 -- Juvenile literature; Toussaint Louverture, -- 1743-1803.; Toussaint Louverture, -- 1743-1803.; 1791-1804; Dominique, 1764? - 1803; Haiti -- History -- Revolution, 1791-1804 -- Juvenile literature; Haiti -- History -- Revolution, 1791-1804.; Haiti; Literature; Biographies; History; Juvenile works; Biographies; Literature